2004
DOI: 10.2193/0022-541x(2004)068[0837:eoehov]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elk Herbivory on Vegetation and Nitrogen Processes

Abstract: We used 35‐year and 4‐year ungulate exclosures to determine the effects of elk (Cervus elaphus) herbivory on above‐ground and below‐ground production and soil fertility on the elk winter range in Rocky Mountain National Park (RMNP), Colorado, USA. We used paired grazed and ungrazed plots to evaluate ungulate herbivory effects in short and tall willow (Salix spp.), aspen (Populus spp.), and upland grass/shrub vegetation associations. We measured nitrogen (N) fluxes (litter deposition, fecal and urinary depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 46 publications
2
45
0
Order By: Relevance
“…Some movement of N down slope is likely to occur through hydrological processes, but since this is a semi-arid system, transport via water could be limited. Just as wild grazers play a crucial role as transporters of organic matter and nutrients in many systems (Frank et al 1994;Walker et al 2003;Schoenecker et al 2004;Holdo et al 2007), we suggest that domestic herds must have played a similar role in the Mongolian steppe for millennia. Currently, the livestock herds largely sort themselves across the topographic gradient, with sheep and goats foraging more often on steeper, upper slopes.…”
Section: Discussionmentioning
confidence: 84%
“…Some movement of N down slope is likely to occur through hydrological processes, but since this is a semi-arid system, transport via water could be limited. Just as wild grazers play a crucial role as transporters of organic matter and nutrients in many systems (Frank et al 1994;Walker et al 2003;Schoenecker et al 2004;Holdo et al 2007), we suggest that domestic herds must have played a similar role in the Mongolian steppe for millennia. Currently, the livestock herds largely sort themselves across the topographic gradient, with sheep and goats foraging more often on steeper, upper slopes.…”
Section: Discussionmentioning
confidence: 84%
“…However, areas used by livestock had comparatively lower belowground investment and higher aboveground investment, a pattern which is related to grazing-mediated variation in plant community composition . These results show that, despite qualitative similarities, it may be diYcult to readily extrapolate insights from natural ecosystems to livestock production systems and vice versa, because quantitative eVects of grazers may vary between diVerent plant communities (e.g., North American prairies, Schoenecker et al 2004; East African savannas, Augustine and McNaughton 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Since the above-and belowground aspects have seldom been studied alongside soil nutrients (Biondini et al 1998;Schoenecker et al 2004), particularly in multi-species natural communities, our results provide a simultaneous assessment of herbivore control over material and energy Xow through grazing ecosystems. The hypothesized eVects of Ungrazed resin N (mg g -1 ) Grazed resin N (mg g -1 ) d 1:1 line herbivores on NAP and nutrient dynamics (de Mazancourt et al 1998) are well supported by Weld experiments (e.g., Ritchie et al 1998;Biondini et al 1998;Chapman et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stewart et al (2006), in a companion study to this paper, reported herbivore optimization by North American elk in this same montane ecosystem, and observed increases in NAPP at low levels of herbivory in forbs, graminoids, and shrubs. Herbivory by elk has also been implicated both in increasing and decreasing rates of nutrient cycling in soils (Singer and Schoenecker 2003;Schoenecker et al 2004).…”
Section: Introductionmentioning
confidence: 99%